Recent Advances in Targeted Drug Delivery Systems: Review Article (Journal of Pharma Insights and Research, 2025)
Targeted drug delivery helps in precise medication delivery to specific organs while minimizing adverse effects on healthy tissues. The evolution of nanocomposite materials has significantly enhanced drug delivery capabilities, offering improved drug-loading efficiency, biocompatibility, and controlled release properties. Various delivery vehicles, including colon-specific systems, liposomes, hydrogels, microfluidics, niosomes, biodegradable particles, microalgae-based carriers, artificial DNA nanostructures, quantum dots, microspheres, and modified plasma proteins, have demonstrated promising results in therapeutic applications. These systems exhibit unique characteristics that facilitate targeted drug administration through different physiological barriers. The integration of smart delivery mechanisms with conventional therapeutic approaches has led to enhanced drug efficacy and reduced systemic toxicity. Recent developments in carrier design and fabrication techniques have improved drug solubility, stability, and bioavailability. The incorporation of targeting moieties and stimuli-responsive elements has enabled precise control over drug release kinetics and tissue specificity. This review work presents recent developments in targeted drug delivery systems, highlighting their mechanisms, applications, and potential impact on future therapeutic strategies.